Quantifying Inorganic Nitrogen Assimilation by Synechococcus Using Bulk and Single-Cell Mass Spectrometry: A Comparative Study - Giardina, Marco; Cheong, Soshan; Marjo, Christopher E.; Clode, Peta L.; Guagliardo, Paul; Pickford, Russell; Pernice, Mathieu; Seymour, Justin R.; Raina, Jean-Baptiste (Frontiers in Microbiology, 2018)
Microorganisms drive most of the major biogeochemical cycles in the ocean, but the rates at which individual species assimilate and transform key elements is generally poorly quantified. One of these important elements is nitrogen, with its availability limiting primary production across a large proportion of the ocean. Nitrogen uptake by marine microbes is typically quantified using bulk-scale approaches, such as Elemental Analyser-Isotope Ratio Mass Spectrometry (EA-IRMS), which averages uptake over entire communities, masking microbial heterogeneity. However, more recent approaches, such as secondary ion mass spectrometry (SIMS), allow for elucidation of assimilation rates at the scale at which they occur: the single cell level. Here, we combine and compare the application of bulk (EA-IRMS) and single-cell approaches (NanoSIMS and Time-of-Flight-SIMS) for quantifying the assimilation of inorganic nitrogen by the ubiquitous marine primary producer Synechococcus. We aimed to contrast the advantages and disadvantages of these techniques and showcase their complementarity in deciphering how the metabolic activity of individual cells can have an impact on ecosystem processes. Our results show that the average nitrogen assimilation rates of Synechococcus cells derived from the three techniques were similar. However, single-cell approaches offered additional layers of information, whereby NanoSIMS allowed for the quantification of the metabolic heterogeneity of individual cells and ToF-SIMS enabled identification and quantification of nitrogen assimilation into specific organic compounds, such as amino-acids. The combined application of these three techniques permitted accurate quantification of the metabolic capacity and chemical transformation dynamics of Synechococcus, one of the smallest and most abundant marine photoautotrophs. We suggest that this coupling of stable isotope-based approaches has great potential to elucidate the metabolic capacity and heterogeneity of microbial cells in natural environments.